Medical and Health Sciences Librarians: New roles and challenges - Abdalhakim Y. M. Bshawi (20683748) (2024)
This presentation explores the field of Medical Librarianship, highlighting the essential roles that Medical and Health Sciences Librarians play in patient care, research, and publication. In addition to traditional library tasks, these specialized librarians contribute significantly to improving health outcomes by facilitating access to vital information and supporting evidence-based practice. The discussion will also address the emerging roles and challenges facing Medical and Health Sciences Librarians in today’s rapidly evolving healthcare landscape. Attendees will gain insights into the critical impact of librarianship in the medical field and the evolving responsibilities that enhance patient care and research initiative. Other Information License: http://creativecommons.org/licenses/by/4.0/